2006
DOI: 10.1097/01.sla.0000205977.74806.0b
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Clinical Assessment of 740 Cases of Surgically Treated Thyroid Cancer in Children of Belarus

Abstract: Total thyroidectomy followed by radioiodine therapy is an optimal treatment strategy that makes it possible to achieve a cure in a vast majority of pediatric patients with differentiated thyroid carcinomas. Risk of recurrence is strongly associated with tumor stage, extent of surgery, the young patient's age, and presence of symptoms at diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

27
208
5
14

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 235 publications
(254 citation statements)
references
References 24 publications
27
208
5
14
Order By: Relevance
“…Some surgeons cite the excellent survival in these patients counterbalancing the morbidity of aggressive surgery, and hence recommend conservative surgery [35,36] Most surgeons prefer to perform a total thyroidectomy for pediatric DTCs [6,7,22,25,29,[37][38][39][40], and the arguments in favour of this are multifold: (a) Multifocal disease occurs in 40% of pediatric PTC, and has a greater risk for recurrence; (b) Pediatric DTC commonly has regional lymph node disease and a greater risk for distant metastasis; (c) Total thyroidectomy will facilitate the future use of radioactive iodine (RAI) where indicated; (d) Postoperative RAI scans and thyroglobulin assays can be best used after total thyroidectomy, these are especially useful in picking pulmonary metastases that may be undetected on initial X-ray. We found that an initial X-ray of chest picked only about 31% of pulmonary metastases [3].…”
Section: Treatment -Surgerymentioning
confidence: 99%
See 3 more Smart Citations
“…Some surgeons cite the excellent survival in these patients counterbalancing the morbidity of aggressive surgery, and hence recommend conservative surgery [35,36] Most surgeons prefer to perform a total thyroidectomy for pediatric DTCs [6,7,22,25,29,[37][38][39][40], and the arguments in favour of this are multifold: (a) Multifocal disease occurs in 40% of pediatric PTC, and has a greater risk for recurrence; (b) Pediatric DTC commonly has regional lymph node disease and a greater risk for distant metastasis; (c) Total thyroidectomy will facilitate the future use of radioactive iodine (RAI) where indicated; (d) Postoperative RAI scans and thyroglobulin assays can be best used after total thyroidectomy, these are especially useful in picking pulmonary metastases that may be undetected on initial X-ray. We found that an initial X-ray of chest picked only about 31% of pulmonary metastases [3].…”
Section: Treatment -Surgerymentioning
confidence: 99%
“…Further support for total thyroidectomy in pediatric thyroid cancers comes from four large cohort studies, which have found that relapse rates are more with lobectomy than with total thyroidectomy [2,29,39,40] To keep the controversy alive, there is a school of thought from Waguespack and Francis, who consider lobectomy for 'low-risk patients with incidental micro-PTC or small (< 1 cm) unifocal tumors as long as pre-and postoperative staging fail to identify multifocal disease in the thyroid or cervical lymph node involvement' [7].…”
Section: Treatment -Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…There was, however, an increase in psychological problems compounded by insufficient communications about radiation effects and by the social disruption and economic depression that followed the break-up of the Soviet Union. Long-term risks for thyroid cancer for those exposed to radiation fallout are continuing around Chernobyl and so far more than 700 children have been operated in Belarus, among whom nearly 60% repeatedly received high-dose radioactive iodine therapy [4,5]. The risks of second primary tumors in these patients have to be evaluated despite of relatively short follow-up period and are of particular important to be followed up carefully.…”
mentioning
confidence: 99%